Improving Visual Literacy Skills of Elementary School Students Against Science Materials in Online Learning - Ilma, Rudhya Nurul; Muktiarni, M.; Mupita, Jonah (Jurnal Abdimas Kartika Wijayakusuma, 2022)
Literacy ability is a fundamental thing that must be possessed by students in facing the global era to be able to meet the needs of life in various situations. The purpose of this study was to examine the mastery of science literacy for grade 5 elementary school students as measured by pictorial questions focused on biology subject. This activity was conducted on fifth grade students at Cibiru 10 Elementary School Bandung. The sample consisted of 10 students who were taken by cluster random sampling method. This activity stage is pre-test - treatment - post-test. The conclusion is that there are still many students who do not know scientific literacy. The results showed that the average post-test score of students was 80.1% greater than the average pre-test score of 40.8%, so the difference was 39.3%. Therefore, Core Competencies can increase students' interest in scientific literacy. students' understanding of the material "respiratory organs" can be improved by increasing core competencies by delivering material via Powerpoint or YouTube platform which is carried out online from the use of the Zoom application with educators.